1970
DOI: 10.13057/biodiv/d040103
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of protease from Bacillus subtilis 1012M15

Abstract: A local strain of Bacillus sp. BAC4, is known to produce penicillin G acylase (PGA) enzyme with relatively high activity. This strain secretes the PGA into the culture medium. However, it has been reported that PGA activity fall and rise during culture, and the activity plummets during storege at -20 0 C, which probably due to usage protease activity of Bacillus sp. BAC4. To study the possible use of Bacillus subtilis 1012M15 as a host cell for cloning the pga gene from Bacillus sp. BAC4, the protease activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Precipatation of protease enzyme isolated from Lactobacillus acidophilus was also found that precipitation with 45% ammonium sulfate gave the highest specific activity, but LBP-1 protease gave a lower activity (0.794 U/mg) then L.acidophilus protease (1.24 U/mg) [9]. LBP-1 protease enzyme has a higher activity than Bacillus substilis 1012M15 (0.475 U/mg) [10].…”
Section: Resultsmentioning
confidence: 99%
“…Precipatation of protease enzyme isolated from Lactobacillus acidophilus was also found that precipitation with 45% ammonium sulfate gave the highest specific activity, but LBP-1 protease gave a lower activity (0.794 U/mg) then L.acidophilus protease (1.24 U/mg) [9]. LBP-1 protease enzyme has a higher activity than Bacillus substilis 1012M15 (0.475 U/mg) [10].…”
Section: Resultsmentioning
confidence: 99%
“…, 0 (2018) E3S Web of Conferences https://doi.org/10.1051/e3sconf /201868010 68 10 1 st SRICOENV 2018 23 23 Bacillus is one type of bacteria that is widely used as a probiotic in aquaculture because of its ability to produce enzymes and antimicrobial components that can inhibit pathogenic bacteria [20]. Bacillus species are very suitable for use because they do not produce toxins, are easy to grow, do not require expensive substrates, Bacillus has the ability to withstand high temperatures, and the absence of metabolic byproducts [21]. Administration of Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…bacteria still in the preparation stage and adjustment to environmental growth conditions, such as nutrient source conditions and substrate environmental conditions. Susanti (2003), stated that in the adaptation phase to the environment the bacteria will hydrolyze the required medium components for metabolism and cell growth. According to Kusumaningati et al (2013), in the slow phase (lag phase) bacteria perform metabolism in preparing and adjusting to the growth conditions in new environments so that there is no significant increase in the number of cells.…”
Section: Bacterial Populationmentioning
confidence: 99%
“…In this phase, the source of nutrients that were available carbon is getting more and more exhausted because it has been exploited by bacteria as a food source. Susanti (2003), stated that in the phase of death, the nutrients was being needed by bacteria are reduced and the results of bacterial excretion have been buried in the medium, thus disrupting the breeding and the next bacterial growth. Anggriani et al (2012), stated that the factors that cause the death of microbial population are the nutrients in the medium are exhausted and no reserve energy in the cell.…”
Section: Bacterial Populationmentioning
confidence: 99%